Análise das implicações da redução da atividade pecuária e aumento da atividade graneleira no estado do Tocantins - Vieira Júnior, Jaime do Espírito Santo (Universidade do Vale do Rio dos Sinos, 2014)
Farming of Tocantins has suffered significant transformations. These changes are linked to federal and state policies to support agricultural frontier (MATOPIBA), to the popular market of commodities export (grains/meat), to public and private agricultural financial programs, to occupation of land in pasture for agricultural activities and migration. In general, the economic impacts of these incentives that generates economic transformations don’t receive the same importance of its creators. Thus, the objective of this study is to evaluate the implications of reducing livestock activity and increased graneleira activity in the state of Tocantins, the last 15 years. To achieve the objectives, a cyclical description of the programs was realized and State interventions to promote agribusiness in Tocantins, where farming dynamics and socioeconomic effects caused were analyzed. The importance of this study is in the understanding of the effects of changes in traditional extensive livestock modifications for the technical modern farming. This study enables a better future planning of Tocantins Agribusiness, mitigating unexpected effects. Governmental and non-governmental secondary data were used for this investigation, semi-structured interviews and visits into rural properties. In this sense, it was established that the Campos Lindos project (Cradle of MATOPIBA-TO), despite the implementation truculence and the economic impacts generated, that put the State in a high level as the biggest soybean producer of the northern region, being this increase, the motivator of the migration process of producers and grain origination companies to traditional areas of livestock in the Central regions and at West of the State. From 2000, a real agricultural modernization occurred in Tocantins, mainly in the municipality of Porto Nacional. During this period, the socioeconomic data of Tocantins suffered positive changes, once there were significant increases of the GDP, GDP per capita, income and HDI, according to the data collected.
Keywords: Impactos econômicos; Matriz produtiva; Impactos da criação de gado; Impactos da produção de grãos; Estado do Tocantins; Economic impacts; Productive matrix; Livestock impacts; Grain production impacts; The state of Tocantins; ACCNPQ::Engenharias::Engenharia de Produção